(untitled) (Bulletin of the International Association for Paleodontology, 2022)
Three prehistoric burials with 12 individuals (three adults and nine subadults) could represent family relationships in a kin-structured small cemetery from a Middle Holocene site in Northeastern Brazil. The absence of collagen for aDNA analysis leaves us to verify the hypothesis of genetic kinship relationships through the analysis of nonmetric dental traits. Our case study presents the analysis of two rare nonmetric dental traits, namely barrel-shaped upper lateral incisors (grades 6 and 7 on UI2 shoveling scale) and premolar odontomes. The relative frequencies of these traits were high in the sample, and statistical interpretation of the data revealed that the co-occurrence of these rare traits is unlikely to happen at random. Thus, their presence in individuals from Toca do Enoque suggest plausible genetic kinship relationships between them.